Porous carbon material and method for producing same

The synthesis of a porous carbon material through a specific reaction and calcination process addresses the challenges of activated carbon electrodes by enhancing electrolyte ion insertion, reducing bulk density, and improving charge storage in electric double layer capacitors.

JP7663669B1Active Publication Date: 2025-04-16SEIWA ELECTRIC MFG CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023218386
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-04-16
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

Activated carbon electrodes for electric double layer capacitors face challenges with complex structures that hinder smooth electrolyte ion insertion and removal, leading to decreased capacity in high output regions and increased bulk density, making the capacitor cell volume large.

Method used

A porous carbon material is synthesized by reacting 2-hydroxy-1,3,5-benzenetricarboxaldehyde with 1,4-diaminobenzene, followed by calcination at 600° C to produce a material with a high pyridine nitrogen content and a spherical shape, which is then used as an electrode material.

Benefits of technology

The resulting porous carbon material exhibits excellent performance as an electrode material for electric double layer capacitors, with increased volume specific capacity and improved charge storage capabilities, while maintaining a compact cell design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663669000001_ABST
    Figure 0007663669000001_ABST
Patent Text Reader

Abstract

The present invention provides a covalent organic framework and a sintered body thereof that can exhibit excellent performance as an electrode material for an electric double layer capacitor, and methods for producing the same. [Solution] A method for producing a porous carbon material includes a synthesis step of synthesizing a covalent organic framework having nitrogen in a ring by a synthetic reaction between 2-hydroxy-1,3,5-benzenetricarboxyaldehyde and 1,4-diaminobenzene, and a calcination step of calcining the covalent organic framework at 600°C±30°C to obtain a porous carbon material in which two large peaks are formed between binding energies of 396 eV to 404 eV in XPS analysis, with the peak on the lower binding energy side being larger than the peak on the higher binding energy side. The porous carbon material obtained by this production method has a pyridine-type nitrogen peak larger than the graphite-type nitrogen peak in XPS analysis, and is formed in a substantially perfect sphere.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous carbon material capable of exhibiting excellent performance as an electrode material for an electric double layer capacitor, and a method for producing the same. [Background technology]

[0002] Activated carbon has conventionally been used as a polarizable electrode for electric double layer capacitors because of its large surface area and excellent electrical conductivity (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-176043 A [Patent Document 2] JP 2011-233845 A [Patent Document 3] JP 2017-155120 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, because activated carbon has a complex and intricate pore structure, when it is used as a polarizable electrode, it becomes difficult for electrolyte ions to smoothly enter and exit the electrode in the high-output region, resulting in a decrease in capacity in the high-output region.

[0005] As an alternative to such activated carbon, a technology capable of forming regular pores has been proposed in which a sintered body of a covalent organic framework obtained by heat-treating a condensate of a boron-containing compound and an alcohol or an aldehyde has been subjected to a thermal treatment (see Patent Document 3).

[0006] However, carbon made for electric double layer capacitors is porous carbon with a large specific surface area, with many micropores around 1 nm in size. Carbon with a large specific surface area has a large bulk density, and when used in a capacitor electrode, it causes the inconvenience of a large cell volume. Also, if the specific surface area is too small, there will be no sites to store electric charge and the capacity will not be expressed, so a certain level of specific surface area is also necessary.

[0007] The present invention has been made in view of the above-mentioned circumstances, and aims to provide a porous carbon material that can exhibit excellent performance as an electrode material for an electric double layer capacitor, and a method for producing the same. [Means for solving the problem]

[0008] A method for producing a porous carbon material according to the present invention for solving the above problems includes a synthesis step of synthesizing a covalent organic framework having nitrogen in a ring by a synthesis reaction between 2-hydroxy-1,3,5-benzenetricarboxyaldehyde and 1,4-diaminobenzene, and a calcination step of calcining the covalent organic framework at 600°C ± 30°C to obtain a porous carbon material in which two large peaks are formed between binding energies of 396 eV to 404 eV according to XPS analysis, and the peak on the lower binding energy side is larger than the peak on the higher binding energy side.

[0009] In the method for producing the porous carbon material, in the synthesis step, a low temperature is used to obtain a covalent organic framework having a small particle size, and a high temperature is used to obtain a covalent organic framework having a large particle size, and a covalent organic framework having a desired particle size is obtained by synthesizing at a desired temperature of 120°C to 180°C.

[0010] The porous carbon material of the present invention for solving the above-mentioned problems is a porous carbon material obtained by the above-mentioned method for producing a porous carbon material, in which the peak of pyridine-type nitrogen is larger than the peak of graphite-type nitrogen as determined by XPS analysis, and the material is formed in a substantially perfect spherical shape.

[0011] The porous carbon material is prepared by kneading the porous carbon material as an active material, acetylene black as a conductive assistant, and polytetrafluoroethylene (PTFE) resin as a binder in a weight ratio of 8:1:1, molding the mixture into a 13 mmφ disk-shaped electrode using a tablet molding machine, and pressing the molded electrode onto a titanium mesh to prepare an electrode test piece. A three-electrode cell is constructed by a three-electrode method using the electrode test piece as a working electrode, Ag / AgCl as a reference electrode, platinum as a counter electrode, and 1M dilute sulfuric acid as an electrolyte, and a constant current of 50 mA (current density of 50 mA / g) is charged to 0 to 0.8 V per weight of the electrode active material, and then discharged to 0.8 to 0 V. The volumetric capacity (C) calculated from the total amount of electricity (ΔQ) flowing during the discharge, the discharge voltage ΔV, and the volume of the electrode active material by the formula (ΔQ / ΔV) / volume of the electrode active material is 158 to 186 F / cm 3 It may be such that:

[0012] The porous carbon material was prepared by kneading the porous carbon material as an active material, acetylene black as a conductive assistant, and polytetrafluoroethylene (PTFE) resin as a binder in a weight ratio of 8:1:1, molding the mixture into a 13 mmφ disk-shaped electrode using a tablet molding machine, and pressing the molded electrode onto a titanium mesh to prepare an electrode test piece. The electrode test piece was used as a working electrode, Ag / AgCl as a reference electrode, platinum as a counter electrode, and 1M dilute A three-electrode cell is constructed by a three-electrode method using sulfuric acid as an electrolyte, and the potential of the three-electrode cell produced using this porous carbon material as a working electrode is swept from 0.2 to 0.8 V at 1.0 mV / sec, and after reaching that potential, it is swept down to 0.8 to 0.2 V at the same sweep rate, so that the oxidation current value at 0.25 to 0.5 V is larger than the oxidation current value at 0.7 V, and the absolute value of the reduction current value at 0.25 to 0.5 V is larger than the absolute value of the reduction current value at 0.7 V.

[0013] The porous carbon material may have a ratio of an integral of an oxidation current value exceeding an oxidation current value at 0.7 V to an integral of an oxidation current value from 0.2 to 0.7 V, mA·V, of 0.37 when measured at a sweep rate of 1.0 mV / sec.

[0014] The porous carbon material may have a ratio of an integral value mA·V of absolute values ​​of reduction current values ​​exceeding the absolute value of the reduction current value at 0.7 V to an integral value mA·V of absolute values ​​of reduction current values ​​from 0.2 to 0.7 V, which is 0.66, when measured at a sweep rate of 1.0 mV / sec.

[0015] The porous carbon material may be prepared by kneading the porous carbon material as an active material, acetylene black as a conductive assistant, and polytetrafluoroethylene (PTFE) resin as a binder in a weight ratio of 8:1:1, molding the mixture into a 13 mmφ disk-shaped electrode using a tablet molding machine, and pressing the molded electrode onto a titanium mesh to prepare an electrode test piece. A three-electrode cell is constructed by a three-electrode method using the electrode test piece as a working electrode, Ag / AgCl as a reference electrode, platinum as a counter electrode, and 1M dilute sulfuric acid as an electrolyte, and the cell is charged to 0 to 0.8 V at a constant current of 50 mA (current density of 50 mA / g) per weight of the electrode active material, and discharged to 0.8 to 0 V, and the volumetric capacity increases during this cycle of 200 cycles.

[0016] In the synthesis step of the method for producing a porous carbon material, the solvent used is not particularly limited, and one or more single solvents or mixed solvents selected from mesitylene, 1,4-dioxane, N,N-dimethylacetone, dichlorobenzene, tetrahydrofuran, methanol, toluene, and acetic acid can be used. For example, 1,4-dioxane may be used alone as a solvent, or a mixed solvent of mesitylene and 1,4-dioxane, N,N-dimethylacetone and dichlorobenzene, tetrahydrofuran and methanol, 1,4-dioxane and toluene, 1,4-dioxane and acetic acid, or mesitylene, 1,4-dioxane, and acetic acid may be used.

[0017] In the method for producing the porous carbon material, in the synthesis step of synthesizing the covalent organic framework, the reaction conditions are not particularly limited as long as the synthesis reaction between 2-hydroxy-1,3,5-benzenetricarboxyaldehyde and 1,4-diaminobenzene forms a shape in which regular cyclic structures such as lattice-like and hexagonal structures are linked together, and a covalent organic framework (COF) having nitrogen in the ring can be synthesized. Operations such as heating, pressurization, decompression, stirring, and cooling are performed as necessary. In the synthesis step, these operations include a combination of a plurality of operations and a stepwise operation. Among them, it has been confirmed that when the temperature for synthesizing the covalent organic framework is, for example, in the range of about 120 to 180° C., the particle diameter of the covalent organic framework formed at a low temperature becomes small, and the particle diameter of the covalent organic framework formed at a high temperature becomes large. Therefore, by synthesizing at a desired temperature, the particle diameter of the covalent organic framework formed can be controlled to obtain a covalent organic framework having a required particle diameter. Furthermore, for example, when 1,4-dioxane is used alone as a solvent, the particle size is larger than when a mixed solvent of 1,4-dioxane and acetic acid is used, so the particle size of the covalent organic framework obtained by synthesis at a desired temperature may be controlled by determining the particle size depending on the solvent used. Figure 1 shows the particle size distribution when synthesized at 120°C when 1,4-dioxane is used alone as a solvent, and the particle size distribution when synthesized at 180°C. The particle size of the covalent organic framework synthesized at 120°C is approximately within the range of 0 to 100 μm (excluding 0).

[0018] The covalent organic framework obtained in the synthesis step is substantially spherical. Here, substantially spherical means that, in image analysis, the radial distance from the center of a circumscribing circle circumscribing the outer periphery of each particle of the covalent organic framework to the actual outer periphery of the particle is measured at intervals of 5 degrees of the central angle of the circumscribing circle, and all of the measured radial distance data falls within ±10% of the average value of the measured radial distance data, and 90% or more of the measured radial distance data falls within ±5% of the average value of the measured radial distance data. FIG. 2(a) shows an electron microscope photograph of the covalent organic framework. The particles of each obtained covalent organic framework correspond to the above-mentioned substantially spherical shape.

[0019] In the above-mentioned method for producing a porous carbon material, in the firing step of firing the covalent organic framework, the firing conditions are not particularly limited as long as the covalent organic framework can be carbonized, and it is preferable to perform firing at a temperature equal to or higher than the decomposition temperature of the covalent organic framework for about 30 minutes to 5 hours. For example, firing can be performed in the range of 600°C ± 30°C, more preferably in the range of 600°C ± 5°C. As shown in FIG. 3, if the firing temperature is too high above 600°C + 30°C, the resulting fired body will have a decreased amount of pyridine-type nitrogen and an increased amount of graphite-type nitrogen. Also, as shown in FIG. 3, if the firing temperature is too low below 600°C - 30°C, the resulting fired body will appear to have a peak of pyridine-type nitrogen, but in reality, the carbon has not been sufficiently fired before the electrical conductivity is developed, and the function of the porous carbon material cannot be fully fulfilled. Table 1 shows the results of measuring the electrical resistance of electrode test pieces prepared using the porous carbon material fired at each temperature.

[0020] [Table 1]

[0021] From these results, it can be confirmed that at 500°C, the material is not sufficiently carbonized to exhibit conductivity, and therefore no conductivity is obtained, whereas conductivity is obtained at 600°C, 800°C, and 1000°C, and that excellent conductivity is obtained when fired at around 600°C in particular.

[0022] This firing may be performed in an atmosphere of normal air, or in an inert gas atmosphere (nitrogen gas or argon gas atmosphere). In this case, the firing atmosphere may be replaced with an inert gas atmosphere at a gas flow rate of 0.1 to 1.0 liters / min. Also, firing may be performed by increasing the temperature from a predetermined temperature at a rate of about 5 to 25°C / min. In addition, in the above temperature range of 600°C±30°C, it is preferable to perform firing in an inert gas atmosphere or under a reduced pressure atmosphere in order to prevent oxidation of the fired body after firing.

[0023] In the porous carbon material thus constructed, as shown in FIG. 3, two large peaks are formed between the bond energies of 396 eV and 404 eV, and the peak of the pyridine-type nitrogen on the lower bond energy side is larger than the peak of the graphite-type nitrogen on the higher bond energy side, resulting in a porous carbon material containing a large amount of the pyridine-type nitrogen. In addition, as shown in FIG. 2(b), the porous carbon material can be made almost perfectly spherical like the covalent organic framework before firing, so that it can have a high bulk density when pressure-molded to produce an electrode. Furthermore, since it can be made almost perfectly spherical like the covalent organic framework before firing, the porous carbon material after firing also becomes a porous carbon material with a particle size proportional to the temperature at the time of synthesizing the covalent organic framework. That is, the particle size of the porous carbon material obtained by firing the covalent organic framework made at a low temperature can be made small, and the particle size of the porous carbon material obtained by firing the covalent organic framework made at a high temperature can be made large. FIG. 1(b) shows the particle size distribution of the porous carbon material obtained by firing the covalent organic framework synthesized at 120°C.

[0024] In addition, since this porous carbon material contains more pyridine-type nitrogen than graphite-type nitrogen, when an electrode is formed from this porous carbon material, a large amount of oxidation current and reduction current can be obtained. Figure 5 shows the cyclic voltammetry (CV) curves obtained when the potential of a three-electrode cell made with this porous carbon material as the working electrode is swept from 0.2 to 0.8 V at 1.0 mV / sec, and then swept from 0.8 to 0.2 V at the same sweep rate. When the internal resistance is low, the voltage rises sharply when voltage is applied and drops sharply when discharged. Therefore, when the capacity of a pure electric double layer is expressed, the CV curve is ideally rectangular, and the closer to a rectangular shape, the lower the internal resistance. In the case of an electrode using the porous carbon material of the present invention, it is thought that the CV curve will form a rectangle in the range width at 0.7 V, where the oxidation current and reduction current values ​​are the smallest. However, it can be confirmed that in the entire range of 0.25 to 0.5 V, the oxidation current and reduction current are larger when a voltage is applied than this range width of 0.7 V, that is, a large oxidation current and a large reduction current are obtained.

[0025] Furthermore, when the electrode formed from this porous carbon material is repeatedly charged and discharged, the volumetric capacity increases significantly up to 50 cycles, and then the volumetric capacity increases gradually from 50 to 100 cycles and from 100 to 150 cycles, although the rate of increase gradually decreases. After about 200 cycles of charging and discharging, an increase in capacity is observed. Figure 6 shows the results of repeated charging and discharging, and the capacity increases for about 200 cycles, and then reaches a maximum value of 186 F / cm at 438 cycles. 3 It can be seen that the charge and discharge can be repeated while the charge approaches

[0026] For these reasons, the porous carbon material of the present invention can obtain a very high charge density and achieve an excellent volumetric capacitance. Table 2 compares the performance of the porous carbon material of the present invention with that of a commercially available product.

[0027] [Table 2]

[0028] As can be seen from Table 2, the porous carbon material of the present invention is capable of storing electric charge with excellent volumetric capacitance, and therefore when configured as an electric double layer capacitor, a more compact product design is possible. Effect of the Invention

[0029] As described above, according to the present invention, the porous carbon material has the largest amount of pyridine type nitrogen among pyridine type nitrogen, graphite type nitrogen, pyrrole type nitrogen and oxide type nitrogen, and can exhibit excellent performance as an electrode material for an electric double layer capacitor. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1(a) is a particle size distribution diagram of the covalent organic frameworks according to Examples 1 and 4 of the present invention, and FIG. 1(b) is a particle size distribution diagram of the porous carbon material according to Example 1. [Diagram 2] FIG. 1(a) is an electron microscope photograph of the covalent organic framework according to Example 1 of the present invention, and FIG. 1(b) is an electron microscope photograph of the porous carbon material according to Example 1 of the present invention. [Diagram 3] 1 is a graph showing the results of X-ray photoelectron spectroscopy (XPS) for the porous carbon material according to Example 1 of the present invention and the porous carbon materials according to Comparative Examples 1 to 3. [Figure 4] 1A is a graph showing the results of nitrogen adsorption / desorption isotherms obtained by measuring the nitrogen adsorption / desorption of a porous carbon material according to Example 1 of the present invention, and FIG. 1B is a graph showing the results of measuring the pore size distribution of the same. [Diagram 5] 1 is a graph showing the measurement results of oxidation current and reduction current by cyclic voltammetry for an electrode test piece using a porous carbon material according to Example 1 of the present invention, an electrode test piece according to Comparative Example 2, and an electrode test piece according to Comparative Example 3. [Figure 6]1 is a graph showing the change in volumetric capacity when the electrode test piece using the porous carbon material according to Example 1 of the present invention is repeatedly charged and discharged. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, an embodiment of the present invention will be described.

[0032] [Example 1] (Powder (synthetic material)) Two types of powder were used: 2-hydroxy-1,3,5-benzenetricarboxyaldehyde (hereinafter referred to as HBTA) having the molecular structure represented by the following formula (1), and 1,4-diaminobenzene (hereinafter referred to as DAB) having the molecular structure represented by the following formula (2).

[0033] [ka]

[0034] (solvent) 1,4-Dioxane was used as the solvent.

[0035] (Synthesis of covalent organic structures) HBTA: 0.024g, DAB: 0.024g, 1,4-dioxane aqueous solution: 25mL were placed in a 50mL hydrothermal synthesis vessel (HU-50: manufactured by San-Ai Scientific Co., Ltd.). After that, the 50mL hydrothermal synthesis vessel (hereinafter referred to as hydrothermal synthesis vessel) was ultrasonically dispersed for 30 minutes, and then heated at 120°C for 24 hours to synthesize a covalent organic framework (synthesis by dehydration condensation). After synthesis, the supernatant was discarded, and 800 mL of low-moisture acetone was added, heated and stirred at 60°C for about 2 hours, left to stand for one day, and the supernatant solution was collected. This process was repeated 7 times, and the powder was dried under reduced pressure at 120°C for 20 hours.

[0036] (Porous carbon materials) The above covalent organic framework was heated in a nitrogen gas atmosphere at a gas flow rate of 0.2 liters / minute from room temperature 25°C at a heating rate of 25°C / minute. After reaching 600°C, it was fired at that temperature for 1 hour, and then naturally cooled to obtain a porous carbon material, which was a fired body of the covalent organic framework.

[0037] (Nitrogen adsorption / desorption measurement (pore specific surface area / pore size distribution measurement)) 0.2 g of the powder of the porous carbon material thus obtained was placed in a sample tube, and the nitrogen adsorption / desorption isothermal curve was measured at liquid nitrogen temperature using a specific surface area / pore distribution measuring device (BELLSORP-miniII: manufactured by Microtrack Bell Co., Ltd.). The specific surface area and pore size distribution were also measured using the analysis program of the same device (Type I (ISO9277) BET automatic analysis). The results are shown in Figure 4. As a result, the porous carbon material thus obtained had a pore specific surface area of ​​479 m 2 / g, average pore diameter 1.0457 nm, pore volume of 1 nm or more (cm 3 / g) was confirmed to be 49.1%.

[0038] (Electron microscope image) The covalent organic framework and the porous carbon material obtained above were subjected to electron microscope photographs under the following conditions. Measurement: Scanning electron microscope (SEM) Measuring device: JSM-6010LA (manufactured by JEOL Ltd.) Measurement conditions: Acceleration voltage 15 kV, secondary electron mode As a result, it was confirmed that the thus obtained covalent organic framework and porous carbon material were both approximately spherical, as shown in FIG.

[0039] [Examples 1-4] (particle size distribution) The synthesis temperature of the covalent organic framework, which was set to 120°C, was changed by 20°C to 140°C (Example 2), 160°C (Example 3), and 180°C (Example 4), but the covalent organic frameworks were synthesized in the same manner as above, and each was fired under the same conditions as above to obtain each porous carbon material. The particle size distribution of each obtained porous carbon material was measured under the following conditions. Measurement principle: Laser diffraction scattering method Measuring device: Shimadzu SALD-2300 Measurement conditions: refractive index 1.75-0.1i (complex refractive index), Dispersion medium used: ethanol, laser transmittance (0.1-0.2) Measurement method: The sample was placed in ethanol, ultrasonically dispersed, then transferred to a special cell and measured. As a result, it was confirmed that the particle size distribution of each porous carbon material thus obtained increases as the synthesis temperature of the covalent organic framework increases from 120° C., and a porous carbon material with the largest particle size distribution is obtained at a synthesis temperature of 180° C. Fig. 1 shows the particle size distribution of the porous carbon material based on the covalent organic framework synthesized at 120° C. (Example 1) and the particle size distribution of the porous carbon material based on the covalent organic framework synthesized at 180° C. (Example 4).

[0040] [Example 1, Comparative Example 1 to Comparative Example 3] (Analysis by X-ray photoelectron spectroscopy (XPS)) In the above porous carbon materials obtained by calcining the covalent organic framework synthesized at 120°C at 600°C, the calcination temperature of the porous carbon materials was changed from 600°C (Example 1) to 500°C (Comparative Example 1), 800°C (Comparative Example 2), and 1000°C (Comparative Example 3), respectively. Except for this, the nitrogen gas flow rate, room temperature, heating conditions, etc. were the same as those described above to obtain each porous carbon material. Each of the porous carbon materials obtained above was analyzed by X-ray photoelectron spectroscopy (XPS) under the following conditions. The results are shown in Figure 3. Measurement model: JPS-901MC (manufactured by JEOL Ltd.) X-ray light source: MgΚα As a result, the porous carbon material according to Comparative Example 1, which was fired at 500°C, had one large peak between the binding energies of 396 eV and 404 eV, and the peaks of pyridine-type nitrogen and graphite-type nitrogen were not sufficiently separated, confirming that the material was not fired sufficiently. The porous carbon material according to Example 1, which was fired at 600°C, had two large peaks between the binding energies of 396 eV and 404 eV, and the peak of pyridine-type nitrogen on the lower binding energy side was larger than the peak of graphite-type nitrogen on the higher binding energy side, confirming that the material contained a large amount of pyridine-type nitrogen. The porous carbon material according to Comparative Example 2, which was fired at 800°C, had two large peaks between the binding energies of 396 eV and 404 eV, and the peak of graphite-type nitrogen on the higher binding energy side was larger than the peak of pyridine-type nitrogen on the lower binding energy side, confirming that the material contained a large amount of graphite-type nitrogen. It was confirmed that the porous carbon material of Comparative Example 3 calcined at 1000°C formed one small peak between binding energies of 396 eV and 404 eV, the pyridine-type nitrogen on the lower binding energy side was decomposed, and the peak of the pyridine-type nitrogen disappeared, and the peak of the graphite-type nitrogen on the higher binding energy side also became smaller than that when calcined at 800°C and was partially decomposed and disappeared.

[0041] (Preparation of electrode test pieces for three-electrode cells) 30 mg of the porous carbon material obtained in Example 1 was used as an active material, 3.75 mg of acetylene black as a conductive assistant, and 3.75 mg of polytetrafluoroethylene (PTFE) resin as a binder were kneaded in a weight ratio of 8:1:1, and molded into a disk-shaped electrode of 13 mmφ using a tablet molding machine. As a result, the electrode thickness was 232 μm. This molded electrode was pressed onto a titanium mesh to prepare an electrode test piece. A three-electrode cell was constructed by the three-electrode method using this electrode test piece as a working electrode, Ag / AgCl as a reference electrode, platinum as a counter electrode, and 1M dilute sulfuric acid as an electrolyte. An electrode test piece was similarly constructed for each of the porous carbon materials according to Comparative Examples 1-3, and a three-electrode cell was constructed using the electrode test piece as a working electrode.

[0042] Using an electrochemical measuring instrument (VSP300 manufactured by Biologic), AC impedance measurements were performed on each electrode test piece using each of the porous carbon materials according to Example 1 and Comparative Examples 1-3 at an applied voltage of 5 mV and a measurement frequency of 1 mHz to 1 MHz to determine the resistance value of each electrode test piece. The results are shown in Table 1. From the results in Table 1, the electrode test piece using the porous carbon material of Comparative Example 1 sintered at 500°C does not have electrical conductivity. This is considered to be because the sintering temperature is low and the material is not sufficiently carbonized to exhibit electrical conductivity. It was also confirmed that the electrode test piece using the porous carbon material of Example 1 sintered at 600°C has a lower resistance value than the electrode test pieces using the porous carbon materials of Comparative Examples 2 and 3 sintered at 800°C or 1000°C.

[0043] (CV curve measurement) Of the electrode test pieces using each of the porous carbon materials prepared above, for each of the electrode test pieces using each of the porous carbon materials according to the remaining Example 1 and Comparative Examples 2-3, excluding Comparative Example 1 in which no electrical conductivity was obtained, the potential of a three-electrode cell prepared using each of the porous carbon materials as the working electrode was swept from 0.2 to 0.8 V at 1.0 mV / sec, and after reaching that potential, the potential was swept from 0.8 to 0.2 V at the same sweep rate, and a cyclic voltammetry (CV) curve was measured. The measurement was performed using an electrochemical measuring device (VSP300 manufactured by Biologic). The results are shown in FIG. 5.

[0044] When the internal resistance is low, it rises sharply when voltage is applied and drops sharply when discharged, so that when the capacity of the pure electric double layer is expressed, the CV curve is ideally rectangular, and the closer to a rectangular shape, the lower the internal resistance. From this, it can be confirmed that the electrode test pieces according to Comparative Examples 2 and 3 have low internal resistance and excellent performance, but in addition, the electrode test piece according to Example 1 has an increased oxidation current value at low voltage, an increased absolute value of the reduction current value at low voltage, and even when compared with the position of 0.7V where the absolute values ​​of the oxidation current value and the reduction current value are the smallest, it can be confirmed that the oxidation current value and the reduction current value at the position of 0.7V are surpassed. Moreover, when it is assumed that the CV curve forms a shape close to a rectangle in the range width of the position of 0.7V where the sum of the absolute values ​​of the oxidation current value and the reduction current value is the smallest, the electrode test piece according to Example 1 according to the present invention has an oxidation current value that is larger than the current value at the position of 0.7V in the entire range of 0.25 to 0.5V, and the absolute value of the reduction current value is larger than the absolute value of the reduction current at the position of 0.7V. Assuming that the CV waveform forms an approximately rectangular shape in the range width at 0.7 V, where the sum of the absolute values ​​of the oxidation current and reduction current values ​​is the smallest, and assuming that any oxidation current value exceeding this is the virtual oxidation current value and any reduction current value exceeding this is the virtual reduction current value, the integral value mA·V of the virtual oxidation current relative to the integral value mA·V of the total oxidation current between 0.2 and 0.7 V was found to be 0.37, and the integral value mA·V of the virtual reduction current relative to the integral value mA·V of the total reduction current between 0.2 and 0.7 V was found to be 0.66.

[0045] (Measurement of volumetric capacity) Using the electrode test piece prepared above, it was charged from 0 to 0.8 V at a constant current of 50 mA (current density of 50 mA / g) and discharged from 0.8 to 0 V. This was repeated, and the volumetric capacity was measured for each cycle. The results are shown in Figure 6. From the results in Figure 6, it can be seen that the volumetric capacity increased with each charge and discharge cycle, with the initial capacity increasing to 81 F / cm. 3 At the 50th cycle, the capacity increased by 95% from the initial capacity to 158 F / cm 3At the 100th cycle, the capacity increased by 108% from the initial capacity to 169 F / cm 3 At the 150th cycle, the capacity increased by 115% from the initial capacity to 174 F / cm 3 At the 200th cycle, the capacity increased by 119% from the initial capacity to 177 F / cm 3 At the 257th cycle, the capacity increased by 122% from the initial capacity to 180 F / cm 3 At the 438th cycle, the capacity increased by 130% from the initial capacity to 186 F / cm 3 It was confirmed that this is the case.

[0046] The present invention can be embodied in various other forms without departing from its spirit or main features. Therefore, the above-described embodiments are merely illustrative in all respects and should not be interpreted as being limiting. The scope of the present invention is defined by the claims and is not limited to the text of the specification. Furthermore, all modifications and changes within the scope of the claims are within the scope of the present invention.

Claims

1. A synthesis step of synthesizing a covalent organic framework having nitrogen in a ring by a synthesis reaction between 2-hydroxy-1,3,5-benzenetricarboxyaldehyde and 1,4-diaminobenzene; and a calcination step of calcining the covalent organic framework at 600°C ± 30°C to obtain a porous carbon material in which two large peaks are formed between binding energies of 396 eV and 404 eV according to XPS analysis, and the peak on the lower binding energy side is larger than the peak on the higher binding energy side.

2. The method for producing a porous carbon material according to claim 1, wherein in the synthesis step, a low temperature is used when obtaining a covalent organic framework having a small particle size, and a high temperature is used when obtaining a covalent organic framework having a large particle size, and synthesis is performed at a desired temperature of 120°C to 180°C to obtain a covalent organic framework having a desired particle size.

3. A porous carbon material obtained by the method for producing a porous carbon material according to claim 1, The peak of pyridine-type nitrogen is larger than the peak of graphite-type nitrogen by XPS analysis. It is formed into a substantially perfect sphere, The porous carbon material as an active material, acetylene black as a conductive assistant, and polytetrafluoroethylene (PTFE) resin as a binder are kneaded in a weight ratio of 8:1:1, and molded into a 13 mmφ disk-shaped electrode using a tablet molding machine. This molded electrode is pressed onto a titanium mesh to prepare an electrode test piece. A three-electrode cell is constructed by a three-electrode method using this electrode test piece as a working electrode, Ag / AgCl as a reference electrode, platinum as a counter electrode, and 1 M dilute sulfuric acid as an electrolyte. The cell is charged with a constant current of 50 mA (current density of 50 mA / g) per weight of the electrode active material up to 0-0.8 V, and then discharged to 0.8-0 V, and the volumetric capacity (C) calculated from the total amount of electricity (ΔQ) flowing during the discharge, the discharge voltage ΔV, and the volume of the electrode active material, by the formula (ΔQ / ΔV) / volume of the electrode active material, is 158-186 F / cm3.

4. A porous carbon material obtained by the method for producing a porous carbon material according to claim 1, The peak of pyridine-type nitrogen is larger than the peak of graphite-type nitrogen by XPS analysis. It is formed into a substantially perfect sphere, The porous carbon material as an active material, acetylene black as a conductive assistant, and polytetrafluoroethylene (PTFE) resin as a binder were mixed in a weight ratio of 8:1:1, and the mixture was molded into a 13 mmφ disk-shaped electrode using a tablet molding machine. This molded electrode was pressed against a titanium mesh to prepare an electrode test piece, and a three-electrode cell was constructed by a three-electrode method using this electrode test piece as the working electrode, Ag / AgCl as the reference electrode, platinum as the counter electrode, and 1 M dilute sulfuric acid as the electrolyte. The potential of the three-electrode cell prepared using this porous carbon material as the working electrode was swept from 0.2 to 0.8 V at 1.0 mV / sec, and after reaching that potential, it was swept from 0.8 to 0.2 V at the same sweep rate.

5. The porous carbon material according to claim 4, wherein the ratio of the integral value of the oxidation current value exceeding the oxidation current value at 0.7 V to the integral value of the oxidation current value from 0.2 to 0.7 V mA·V when measured at a sweep rate of 1.0 mV / sec is 0.

37.

6. The porous carbon material according to claim 4, wherein the ratio of the integral mA·V of the absolute values ​​of the reduction current values ​​exceeding the absolute value of the reduction current value at 0.7 V to the integral mA·V of the absolute values ​​of the reduction current values ​​from 0.2 to 0.7 V when measured at a sweep rate of 1.0 mV / sec is 0.

66.

7. A porous carbon material obtained by the method for producing a porous carbon material according to claim 1, The peak of pyridine-type nitrogen is larger than the peak of graphite-type nitrogen by XPS analysis. It is formed into a substantially perfect sphere, The porous carbon material as an active material, acetylene black as a conductive assistant, and polytetrafluoroethylene (PTFE) resin as a binder are kneaded in a weight ratio of 8:1:1, and molded into a 13 mmφ disk-shaped electrode using a tablet molding machine. This molded electrode is pressed onto a titanium mesh to prepare an electrode test piece. A three-electrode cell is constructed by a three-electrode method using this electrode test piece as a working electrode, Ag / AgCl as a reference electrode, platinum as a counter electrode, and 1 M dilute sulfuric acid as an electrolyte, and charged to 0-0.8 V at a constant current of 50 mA (current density of 50 mA / g) per weight of the electrode active material, and discharged to 0.8-0 V, and this cycle is repeated for 200 cycles, during which the volumetric capacity of the porous carbon material increases.

Citation Information

Patent Citations

  • Activated carbon for electric double layer capacitor

    JP2011176043A

  • Polarizable electrode material for electric double layer capacitor with improved voltage resistance, and electric double layer capacitor using the same

    JP2011233845A

  • Method for producing covalent organic structure and covalent organic structure

    JP2017155120A

  • Spherical carbon particle containing nitrogen element and process for producing spherical carbon particle

    JP2018115103A

  • Fired body of covalent organic framework and producing method thereof

    JP2020040857A